α-glucosidase inhibitors isolated from Mimosa pudica L. - Tasnuva, S. T.; Ahmed, Qamar Uddin; Ghafoor, Kashif; Ferdosh, Sahena; Jahurul, M. H. A.; Rukshana, A. H.; Md. Jaffri, Juliana; Y. Al-Juhaimi, Fahad; Jalifah, L.; Jalal, K. C. A.; Ali, Md. Eaqub; Sarker, Md Zaidul Islam (Taylor and Francis (UK), 2017)
The aim of the study was to isolate digestive enzymes inhibitors from Mimosa pudica through a bioassay-guided fractionation approach. Repeated silica gel and sephadex LH 20 column chromatographies of bioactive fractions afforded stigmasterol, quercetin and avicularin as digestive enzymes inhibitors whose IC50 values as compared to acarbose (351.02 ± 1.46 μg mL−1) were found to be as 91.08 ± 1.54, 75.16 ± 0.92 and 481.7 ± 0.703 μg mL−1, respectively. In conclusion, M. pudica could be a good and safe source of digestive enzymes inhibitors for the management of diabetes in future.